Fabry disease - Gómez Luján, Martín (2018)
ABSTRACT Fabry disease is a lysosomal storage disease caused by alpha galactosidase A enzyme deficiency. The pattern of inheritance is X-linked. The clinical presentation has a variety of symptoms and signs; and a classic clinical variant and non-classical clinical variants such as renal or cardiac have been described. The diagnosis is clinical and laboratory and even molecular and in some cases histology of the compromised organ is needed. The treatment in recent years remains symptomatic therapy and with enzyme replacement therapy; although chaperones are already available for the treatment of a group of patients with "amenable" mutations and they are studying gene therapy and nanotechnology. It must have a multidisciplinary approach, given the variety of symptoms and signs in its presentation. Early detection and early initiation of therapy could improve quality of life and limit the progression of the disease; and finally genetic counseling should always be considered. Key words: Fabry disease, Alpha galactosidase, Chronic kidney disease. (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1595